Cancer Statistics for Hispanics/Latinos, 2018 - Miller, Kimberly D.; Goding Sauer, Ann; Ortiz, Ana P.; Fedewa, Stacey A.; Pinheiro, Paulo S.; Tortolero‐Luna, Guillermo; Martinez‐Tyson, Dinorah; Jemal, Ahmedin; Siegel, Rebecca L. (CA: a cancer journal for clinicians, 2018)
Cancer is the leading cause of death among Hispanics/Latinos, who represent the largest racial/ethnic minority group in the United States, accounting for 17.8% (57.5 million) of the total population in the continental United States and Hawaii in 2016. In addition, more than 3 million Hispanic Americans live in the US territory of Puerto Rico. Every 3 years, the American Cancer Society reports on cancer occurrence, risk factors, and screening for Hispanics in the United States based on data from the National Cancer Institute, the North American Association of Central Cancer Registries, and the Centers for Disease Control and Prevention. For the first time, contemporary incidence and mortality rates for Puerto Rico, which has a 99% Hispanic population, are also presented. An estimated 149,100 new cancer cases and 42,700 cancer deaths will occur among Hispanics in the continental United States and Hawaii in 2018. For all cancers combined, Hispanics have 25% lower incidence and 30% lower mortality compared with non‐Hispanic whites, although rates of infection‐related cancers, such as liver, are up to twice as high in Hispanics. However, these aggregated data mask substantial heterogeneity within the Hispanic population because of variable cancer risk, as exemplified by the substantial differences in the cancer burden between island Puerto Ricans and other US Hispanics. For example, during 2011 to 2015, prostate cancer incidence rates in Puerto Rico (146.6 per 100,000) were 60% higher than those in other US Hispanics combined (91.6 per 100,000) and 44% higher than those in non‐Hispanic whites (101.7 per 100,000). Prostate cancer is also the leading cause of cancer death among men in Puerto Rico, accounting for nearly 1 in 6 cancer deaths during 2011‐2015, whereas lung cancer is the leading cause of cancer death among other US Hispanic men combined. Variations in cancer risk are driven by differences in exposure to cancer‐causing infectious agents and behavioral risk factors as well as the prevalence of screening. Strategies for reducing cancer risk in Hispanic populations include targeted, culturally appropriate interventions for increasing the uptake of preventive services and reducing cancer risk factor prevalence, as well as additional funding for Puerto Rico‐specific and subgroup‐specific cancer research and surveillance.